MANAJEMEN RlSIKO PEMBIAYAAN MUDHARABAH PADA PERBANKAN SYARIAH - M Nasih; Nisful Laila; - Dewikarina (Trunojoyo University of Madura, 2013)
Mudharabah is a partnership contract with the principle of profit sharing which is applied in Islamic banks. The data financing on Islamic Banking Development Report in the last four years shows murabahah financing has a large portion of financing with a stable condition of development, on the contrary mudharabah financing has a small financing and declining percentage. The purpose of this research is to determine risk management of mudharabah financing in Islamic banking with a limit to the causes of the low number of mudharabah financing, the common problems and solutions.The method of the research is using a qualitative approach with a case study strategy. The informants are obtained from 3 Islamic Banks or Bank Umum Syariah (BUS), namely BMI, BSM and BNIS. The data collection is conducted by linking the questions and the obtained data with the conclusion of the result of interview data with the Account Officer from the 3 Islamic Banks; BMI, BSM, and BNIS.The result of the research shows that the low number of mudharabah financing is caused by the big considerable risk, it is the risk of losses, particularly on the income of the bank. Meanwhile, the problem that commonly occur is non-performing financing because of the side streaming and manipulated data. The solution is restructuring to the bank's customer who has a good faith, on the contrary with different personality of bank's customer will be put into the collateral execution.